Developing UK Defence Rehabilitation research priorities: a 2020 clinical practitioner engagement exercise. Issue 4 (26th November 2020) - Coppack, Russell J; Ladlow, P; Bennett, A N
Abstract : Introduction: Establishing research priorities help to address knowledge gaps and exploit emerging opportunities to develop a clinical evidence base. The previous clinical engagement exercise to determine UK Defence Rehabilitation practitioner-based research priorities was conducted in 2014. The aim of this article is to (1) describe how research priorities are established for UK Defence Rehabilitation; (2) review, reassess and rate the priorities highlighted and set by rehabilitation practitioners following the 2014 survey and (3) identify new rehabilitation research themes and topics reflecting 2020 priorities. Methods: Stage 1: delegates (n=72) at the October 2019 Defence Medical Services Rehabilitation Conference participated in a series of focus group workshops. Stage 2: an online survey circulated through the military chain of command to all Defence Primary Health Care clinical rehabilitation staff. Stage 3: a thematic analysis of all survey submissions yielding a ranked order of priority by topic. Results: 165 clinical rehabilitation staff completed an online survey. 'Rehabilitation outcomes', 'Psychological factors in rehabilitation' and 'Residential/Inpatient treatment paradigm' emerged as three clear research priorities across all three tiers of UK Defence Rehabilitation. New research priorities emerging from the 2020 survey were 'lifestyle factors during rehabilitation', 'management of pain during rehabilitation' and 'anterior knee pain'. Conclusion: It is essential that funding directed to musculoskeletal rehabilitation focuses on the highest research priorities in the field to ensure optimum health return on investment. The results of this survey will assist in guiding the clinical research being conducted within UK Defence Rehabilitation over the next five years.